TESTİNG THE EXPECTATİON HYPOTHESİS FOR FRAGİLE EİGHT COUNTRİES (Third Sector Social Economic Review, 2020)
The financial crisis that occurred in the United States (USA) in 2008 and Europe in 2015 caused excessive fluctuations in all markets. It is important to estimate how the interest rates will be shaped in the long term in this situation where the investment environment comes. Understanding the relationship between interest rates of financial instruments of different term times is significant in this context for future estimates. Explanation of the maturity structure with the expectation hypothesis (EH) is a method frequently used in the literature. According to this theory, long-term interest rates are the result of short-term interest rates available in the market. In this study, it is aimed to test the EH by Kugler’s (1990) Approach which is based on VAR Model, by analyzing the 3-month deposit interest and 10-year bond yield for Fragile Eight countries for various periods. According to the research findings, while the expectation hypothesis for Russia, Indonesia is not found valid; the expectation hypothesis in South Africa, Chile, Turkey, India, Brazil is seen as important.
Keywords: expectation hypothesis; fragile eight; term structure; interest rate